2022
DOI: 10.5194/acp-22-4985-2022
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced soot particle ice nucleation ability induced by aggregate compaction and densification

Abstract: Abstract. Soot particles, acting as ice nucleating particles (INPs), can contribute to cirrus cloud formation, which has an important influence on climate. Aviation activities emitting soot particles into the upper troposphere can potentially impact ice nucleation (IN) in cirrus clouds. Pore condensation and freezing (PCF) is an important ice formation pathway for soot particles in the cirrus regime, which requires the soot INP to have specific morphological properties, i.e., mesopore structures. In this study… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 98 publications
5
34
0
Order By: Relevance
“…The understanding of the lower size threshold for soot ice formation is important, given the strong particle size dependence of (soot) ice nucleation and that the Aitken mode dominates size distribution from aviation soot emissions and other hightemperature combustion sources. A recent study reported that small-sized (< 100 nm) soot particles, even as active as uncoated FW200 in this study, nucleate ice homogeneously for T < HNT (Gao et al, 2022a), implying that H 2 SO 4 -coated soot particles of a size smaller than 100 nm require homogeneous freezing conditions to form ice in the cirrus cloud regime. Moreover, this study contributes to the climate impact evaluation of soot emissions.…”
Section: Discussionsupporting
confidence: 45%
“…The understanding of the lower size threshold for soot ice formation is important, given the strong particle size dependence of (soot) ice nucleation and that the Aitken mode dominates size distribution from aviation soot emissions and other hightemperature combustion sources. A recent study reported that small-sized (< 100 nm) soot particles, even as active as uncoated FW200 in this study, nucleate ice homogeneously for T < HNT (Gao et al, 2022a), implying that H 2 SO 4 -coated soot particles of a size smaller than 100 nm require homogeneous freezing conditions to form ice in the cirrus cloud regime. Moreover, this study contributes to the climate impact evaluation of soot emissions.…”
Section: Discussionsupporting
confidence: 45%
“…Fresh 400 nm PR90 particles freeze homogeneously at 233 K but nucleate ice far below Shom conditions via the PCF mechanism for T ≤ 228 K as containing suitable mesopores to PCF processes. 16 For denuded 400 nm PR90 particles, the onset Si decreases by more than 0.12 at 233 K, compared to the fresh sample. However, the IN enhancement becomes smaller and the onset Si values of PR90 soot are within error bars at lower T (≤ 228 K).…”
Section: Fw200mentioning
confidence: 94%
“…In this study, we modified the mathematical approach for retrieving PSD based on DVS isotherms developed by Wheeler 48 and Shkol'nikov and Sidorova 49 and a high order polynomial fitting method was used to calculate a smoother desorption isotherm function of RHw. For detailed formulation, we refer the reader to Mahrt et al 15 and Gao et al 16 TEM: Size-selected mBlack and mBrown particles (400 nm) with and without thermal denuding were also sampled for transmission electron microscopy (TEM, JEOL-1400+, JEOL Ltd., Tokyo, Japan, operated at 120 kV) analysis.…”
Section: Sample Characterisation Measurementsmentioning
confidence: 99%
See 2 more Smart Citations